Pengaruh Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa: Studi Kasus Se Kecamatan Suwawa Timur Kabupaten Bone Bolango - Ferra Meilisa; Mattoasi; Muliyani Mahmud (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of human resource competency and the use of information technology on the accountability of village fund management. The research method used in this research is a quantitative method with an associative quantitative approach. The data used is primary data obtained from distributing questionnaires to Village Heads, Village Secretaries, Heads of Finance and BPD who have served in the last 3 years in East Suwawa District, Bone Bolango Regency. This research involves 3 variables, namely 2 independent variables and 1 dependent variable. Where the independent variable (X1) is Human Resource Competency, the independent variable (X2) is Information Technology Utilization and the dependent variable (Y) is Village Fund Management Accountability. Data analysis in this study used multiple linear regression. The results of the research show 1) Human Resource Competence has a positive and significant effect on accountability in village fund management, 2) The use of information technology has a positive and significant effect on accountability in village fund management, and 3) simultaneously human resource competence and the use of information technology have a positive and significant effect. significant to the accountability of village fund management.